Optimization and Comprehensive Utilization Technology of Waste Incineration Power Generation System - Lijun WANG (发电技术)
Waste incineration power generation has gradually become PPP project led by local governments. With the deepening of the national energy strategy, it is an urgent task to accelerate the research and development of energy-saving and emission reduction technology and the industrialization promotion by relying on scientific and technological innovation. Under multiple pressures, such as high project construction standards and financing requirements, low waste disposal fees and long investment recovery period, through the gradual and itemized design optimization of the waste incineration power generation system and the efficient and deep utilization of resources by using the latest technology, the construction cost of the project could be effectively reduced, the operation economy of the project could be improved, and the waste reduction, innocuous and recycling could be realized, it has reference value to the long-term healthy development of garbage power generation.